Formação de Professores de uma Clínica-Escola Especializada para Crianças com Diagnóstico do Transtorno do Espectro Autista: contribuições da perspectiva histórico-cultural - Comparin, Karen Andréa (2024)
Considering the growing number of children diagnosed with Autism Spectrum Disorder (ASD), challenging Education, and having the teacher-student dyad as fundamental in this process, the present research aimed to analyze the development of teacher's continuous formative process, based on a historical-cultural perspective, aiming to expand their emancipation on the work with children diagnosed with Autism Spectrum Disorder. The specific objectives were: Analyze the contributions of the historicalcultural perspective to the process of children and adults humanization and emancipation; Identify in a research based on a historical-cultural perspective, on the Brazilian Digital Library of Theses and Dissertations (BDTD), CAPES and LILACS Periodicals, the contributions to understanding the continuous formative process of teacher's; Analyze the impact of a continuous formative process of teacher's in the learning process of children diagnosed with ASD. The study, involving 14 teacher's, was carried out at the Autistic Spectrum Disorder School Clinic (CETEA), in the city of Cascavel – PR. The process included meetings addressed, among other topics: philosophical assumptions, from a historical-cultural perspective, articulating with the curriculum of the municipal education network; concepts of humanization and emancipation; higher psychological functions; zone of imminent development; and periodization of psychic development. Tasks were developed, based on Activity Theory, to be applied in teacher's daily school life, with a focus on autistic students, which were later used to analyze their effects. Content Analysis was used to organize and analyze the data, aiming to capture the teaching movement. From the State of Knowledge and based on the theoretical foundation of the study, the results were analyzed according to the following categories: Limits and Possibilities of Teacher's formative process, Guide Activity and Teaching-Learning Process. An advance was observed in the teacher's theoretical thinking during the formative process, bringing elements of theory to support practice in a dialectic relationship, demonstrating a greater understanding and consequently greater clarity of his responsibility for the entire teaching and learning process of the student, expanding the initial conception, mainly restricted to ASD conditions. In conclusion, the thesis defended is confirmed as a continuous formative process based on a historical-cultural theory can generate transformations in the teacher's involved, who expand their emancipation as they appropriate the foundations of their pedagogical work.